2020
DOI: 10.1016/j.cmet.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Human Brown Adipocyte Thermogenesis Is Driven by β2-AR Stimulation

Abstract: Highlights d A therapeutic dose (50 mg) of mirabegron does not stimulate human BAT thermogenesis d Human brown adipocytes lack b 3 -AR and do not respond to mirabegron in vitro d Norepinephrine-induced respiration is driven by b 2 -AR, which co-localizes with UCP1 d b 2 -AR is the main target for pharmacological activation of human brown adipocytes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
254
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 242 publications
(264 citation statements)
references
References 53 publications
6
254
2
2
Order By: Relevance
“…CC-BY-NC-ND 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is human brown adipocytes (43). UCP1 mRNA expression in human adipocytes was also increased by PHDi-treatment (Figure 3d), suggesting that PHDi could induce a beiging-gene signature in human WAT.…”
Section: Pan-phd Inhibition Inducesmentioning
confidence: 84%
“…CC-BY-NC-ND 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is human brown adipocytes (43). UCP1 mRNA expression in human adipocytes was also increased by PHDi-treatment (Figure 3d), suggesting that PHDi could induce a beiging-gene signature in human WAT.…”
Section: Pan-phd Inhibition Inducesmentioning
confidence: 84%
“…Therefore, we cannot exclude that β 3 ‐agonism in BAT cells 54,55 may stimulate tissue thermogenesis without necessarily affecting perfusion. Stimulation of blood flow and BAT in humans may also involve different receptors than for rats 56,57 …”
Section: Discussionmentioning
confidence: 99%
“…Although there are many similarities between rodent and human BAT depots, notable differences also exist. Whereas the activation of murine BAT is mediated by b3-AR, a recent study revealed that b2-AR is the relevant adrenoceptor which activates human BAT (4). This underscores the need for caution when translating new advances generated by preclinical studies to humans.…”
Section: Perspectivesmentioning
confidence: 99%